KARAKTERISTIK MORTAR MENGGUNAKAN BIOPOZZOLAN SEBAGAI PENGGANTI SEBAGIAN SEMEN - Nunung Martina; Seira Diwama Cathelina; Zahara Tunnur (Politeknik Negeri Jakarta, 2019)
AbstractThis research uses Bio-pozzolan which consist of ASP and lime as a substitute for cement which is expected to be used in the manufacture of mortar. Mortar mixtures were tested with a total of 70 specimens, including compressive strength of 45 specimens according to SNI 03 – 6825 – 2002, flexural strength of 15 specimens according to ASTM C 580 – 02, and changes in length of 10 specimens according to ASTM C 157 – 93. Mortar specimens with a comparison ratio of 1 PC : 3 Aggregate, the adhesive material is partially replaced with a Bio-pozzolan adhesive consisting of ASP and lime. The amount of cement substitution with Bio-pozzolan is 17,5% of the weight of cement. In this research the variation of bio-pozzolan as follows; variation 1 (0% Bio-pozzolan), variation 2 (50% lime: 50% RHA), variation 3 (60% lime: 40% RHA), variation 4 (70% lime: 30% RHA), variation 5 (80% lime: 20% RHA). The results showed the composition of Bio-pozzolan variation 2 produces compressive strength with a value of 20,889 MPA, flexural strength is 6,3735 MPA, and a value of change in length with the lowest shrinkage expansion. This Bio-pozzolan Mortar variation 2 is included into the mortar type M.Keywords : Rice Husk Ash, Quicklime, Mortar, compressive strength, flexural strength, length change.AbstrakPenelitian ini menggunakan Biopozzolan yang terdiri dari abu sekam padi (ASP) dan kapur sebagai pengganti sebagian semen yang diharapkan dapat dimanfaatkan dalam pembuatan mortar. Campuran mortar yang diuji dengan total benda uji sebanyak 70 buah, meliputi kuat tekan 45 benda uji sesuai standar SNI 03 – 6825 – 2002, kuat lentur 15 benda uji sesuai standar ASTM C 580 – 02, dan perubahan panjang sebanyak 10 benda uji sesuai standar ASTM C 157 – 93. Benda uji berupa mortar dengan perbandingan komposisi 1 Pc ; 3 Psr, bahan perekat isi diganti sebagian dengan perekat Biopozzolan yang terdiri dari ASP dan kapur. Jumlah substitusi semen dengan biopozzolan sebesar 17,5% dari berat semen. Pada pebelitian ini Biopozzolan divariasikan sebagai berikut; variasi 1 (0% Biopozzolan) , variasi 2 (50% Kapur : 50% ASP), variasi 3 (60% Kapur : 40% ASP), variasi 4 (70% Kapur : 30% ASP), variasi 5 (80% Kapur : 20% ASP). Hasil penelitian didapatkan komposisi Biopozzolan variasi 2 menghasilkan kuat tekan dengan nilai 20,899 Mpa dan kuat lentur dengan nilai 6,3735 MPa serta nilai perubahan panjang dengan muai susut paling rendah. Mortar Biopozzolan variasi 2 ini termasuk tipe M.Kata kunci : Abu Sekam Padi, Kapur, Mortar, kuat tekan, kuat lentur, perubahan panjang.